In Vitro Survival of Scabies Mites - Arifullah Maj, Muhammad Adeel Siddique, Lt. Col. Majid Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The correct treatment and management of scabies is expensive and time-consuming, and may have a negative impact on patients and their families. The aim of the current study was to investigate the effects of permethrin 5% cream on scabies mites, and explore mite survival times outside the human body Patients and Methods: This was Quasi Experimental Study, carried out the Department of Dermatology, Combined Military Hospital, Abbottabad, Pakistan, from March 2022 to August 2022. A total of 60 scabies mites were taken from 60 patients reporting at OPD during the study period. A total of 60 petri dishes were divided in to two groups, 30 petri dishes coated with permethrin 5% cream were in the treatment group while 30 plain petri dishes were included in the control group. One scabies mite was placed in each dish. Observation was made at baseline and then 3, 4, 5, 6, 7, 8 and 12 hours from baseline. Death of the mite was decided when all the leg movements were ceased. Results: The results of the study showed that after 8 hours 60% of the scabies mites survived in treatment group while 70% survived in control group. After 12 hours, 16.66% of mites in the treatment group and 60% in the control group were survived. (p-value= 0.019) Practical implication: The purpose of this study was not only to treat the patient but also to take measures to ensure that the prevalence is stopped from individual to individual, as clothes and bed linen also contains the mites and surrounding environment also needs proper management. The aim of our study was to find survival time of scabies mites present in our Pakistani population in vitro to the effects of 5% permethrin cream, which is the most widely used treatment in Pakistan for scabies mites. This will help to advice the patients accordingly for exact application time required for the drug and the time when the mites are actually died. Conclusion: Based on these results, we suggest that 5% permethrin topical cream needs to be left on body for at least 12 hours before patient wash it off. Keyword: In Vitro Survival, Scabies, Permethrin, Mal-Nutrition, Immigration, Dementia, Families